Kavousi I : the archaeological survey of the Kavousi Region - Haggis, Donald C. (Prehistory monographs, 2005)
"The initial volume of the Kavousi Excavation Series, which presents the final report of the Kavousi project, a program of archaeological investigation around the modern village of Kavousi in eastern Crete. Subsequent volumes will publish the results of the 1987-1992 excavations at the Vronda and Kastro sites in the Siteia Mountains above Kavousi and of the cleaning and new study of the excavations of Harriet Boyd in 1900 and 1901"--Page xxvii